Militerisasi Pulau Buatan di Laut China Selatan oleh Tiongkok: Implikasi terhadap Keamanan Maritim Negara-negara di Kawasan Asia Tenggara - Andi Alya Khairunnisa; Agussalim Burhanuddin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The South China Sea is a strategic water area connecting East Asia, the Pacific Ocean, and the Indian Ocean, and is the main route for around 30 percent of international trade shipping. This area is also rich in energy resources, such as natural gas and petroleum. However, in recent decades, the South China Sea has become the center of territorial disputes due to unilateral maritime claims by China through the Nine Dash Line principle which covers up to 90 percent and is contrary to the Law of the Sea. China even builds artificial islands equipped with military infrastructure, which increases tensions in the region. Through the approach of the realism paradigm, as well as the theory of complex regional security and maritime security as well as literature analysis, this article discusses the implications of China's artificial island construction on maritime security in Southeast Asia, especially for countries such as Vietnam, the Philippines, Malaysia, and Brunei Darussalam. This article emphasizes that China's actions have implications that greatly disrupt the stability of maritime security for countries in the region located in the South China Sea waters.